Association of OAS1 and MxA variants with COVID-19 in Pakistani patients - Naila Shaikh; Feriha Fatima Khidri; Hina Shaikh; Amber Mahmood; Atif Sitwat Hayat; Yar Muhammad Waryah; Tarachand Devrajani; Ikram Din Ujjan; Ali Muhammad Waryah (Journal of Infection in Developing Countries, 2024)
Introduction: Coronaviruses, a family of enveloped RNA viruses, have been implicated in various clinical disorders including coronavirus disease 2019 (COVID-19). Host genetic factors, including the OAS1 and MxA gene variants may have a role in determining susceptibility to viral infections. Understanding the genetic factors involved in unraveling COVID-19`s diverse clinical outcomes is critical for disease management. This study investigated the impact of OAS1 rs2660 and MxA rs2071430 genotypes on COVID-19 susceptibility and severity among Pakistani patients.